Enhancing Emotion Regulation among Orphanage Adolescents through Mindfulness Training and Expressive Writing: A Community Service Initiative - Muhammad Habib Alwi; Tuti Rahmi (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve emotion regulation among adolescents residing in an orphanage through mindfulness training and expressive writing while evaluating the effectiveness of these interventions. A quasi-experimental pretest-posttest design with a control group was employed involving 35 adolescents aged 12–18 years, who were allocated to a mindfulness group (n = 13), an expressive writing group (n = 12), and a control group (n = 10). The interventions were delivered through brief, structured group sessions facilitated within the orphanage setting. Emotion regulation was assessed using the Emotion Regulation Questionnaire (ERQ), adapted from Gross and John (2003), which measures the dimensions of cognitive reappraisal and expressive suppression. Data were analyzed using Welch's ANOVA followed by the Games-Howell post hoc test. Pretest scores showed no significant differences among the groups, indicating comparable baseline conditions. In contrast, posttest results revealed significant between-group differences, with both intervention groups achieving significantly higher emotion regulation scores than the control group, whereas no significant difference was found between the mindfulness and expressive writing groups. These findings suggest that mindfulness training and expressive writing are practical, low-cost psychosocial interventions for strengthening emotion regulation among adolescents in orphanage settings. Although the program was limited by a relatively small sample size, the quasi-experimental design, a short intervention period, and the absence of follow-up assessment, both interventions demonstrate potential for integration into routine psychosocial services through basic training for caregivers and orphanage staff, thereby supporting sustainable implementation with minimal resources.